2018
DOI: 10.1029/2018ja025725
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Extent and Temporal Correlation of Chorus and Hiss: Statistical Results From Multipoint THEMIS Observations

Abstract: The spatial localization of whistler mode waves, determined by their generation process, propagation, and damping, is important for assessing the efficiency of wave-particle interactions and the dynamics of the radiation belts. We use 11 years of multipoint wave measurements in 2007-2017 from five Time History of Events and Macroscale Interactions during Substorms (THEMIS) spacecraft covering L = 2-10 at low magnetic latitudes over all magnetic local times (MLTs) to characterize both the instantaneous spatial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
100
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(116 citation statements)
references
References 77 publications
15
100
1
Order By: Relevance
“…It is worth noting that the requirement for strong azimuthal density gradients in the form of plumes provides an explanation for the spatial structure observed by Agapitov et al (2018), who found that correlation between chorus and hiss waves was observed most frequently between 12 and 16 MLT. This spatial limitation is also consistent with the direct observation of concurrent, or slightly delayed, enhancements between chorus and hiss measured between 13 and 17 MLT by Bortnik et al (2009) and between 12 and 13 MLT by Li et al (2015).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…It is worth noting that the requirement for strong azimuthal density gradients in the form of plumes provides an explanation for the spatial structure observed by Agapitov et al (2018), who found that correlation between chorus and hiss waves was observed most frequently between 12 and 16 MLT. This spatial limitation is also consistent with the direct observation of concurrent, or slightly delayed, enhancements between chorus and hiss measured between 13 and 17 MLT by Bortnik et al (2009) and between 12 and 13 MLT by Li et al (2015).…”
Section: Discussionmentioning
confidence: 92%
“…Further investigation revealed chorus at larger radial distances, ∼10 R E , could be a source of plasmaspheric hiss with observed time delays of 5–8 s, consistent with propagation times predicted by ray tracing (Li et al, ). Agapitov et al () showed substantial correlation between chorus and hiss wave power observed by the Time History of Events and Macroscale Interactions during Substorms (THEMIS) mission, occurring most frequently in the post‐noon sector, with ∼20% of chorus observed between 12 and 16 in magnetic local time (MLT) being well correlated with hiss waves observed inside of the plasmasphere immediately afterward. Through extensive modeling efforts it has also been demonstrated that this chorus‐to‐hiss mechanism could reproduce the frequency range, wave power, and the spatial structure of plamsaspheric hiss (e.g., Chen, Bortnik, et al, , ; Chen, Li, et al, ; Meredith et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Chorus waves are generated via the instability created by the temperature anisotropy of these hot electrons, and we present evidence that the spatial location of chorus wave power follows the changing access and drift history of these source electrons. Agapitov et al, 2018), furthering showing the importance in understanding the generation of chorus waves in the afternoon sector. To our knowledge, our results are the first showing the storm phase progression over MLT and Lshell with direct chorus observations.…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, from THEMIS FBK statistics, Agapitov et al (2018) found that cluster scale chorus waves with larger B w have smaller scale sizes, which may be consistent with our results, since larger B w chorus waves are more likely observed near the equator region, especially in the nightside magnetosphere (W. Li et al, 2009). Moreover, the scale size of cluster scale chorus waves is larger on the dayside than on the nightside, which is suggested to be caused by the fact that injected energetic electrons spread wider as they drift from the nightside to the dayside (Agapitov et al, 2018). Thus, it is not surprising that a relatively small scale size of chorus waves,~100 km, was reported by Santolík and Gurnett (2003) near 21 MLT.…”
Section: Summary and Discussionmentioning
confidence: 99%